Game meat characteristics - Lozinski, Ivan; Strashynskyi, Igor (My University, 2013)
Market of Ukraine represents a wide range of meat products made from traditional raw meat. However, there are segment of consumers who are more and more looking for new gourmet products. A production of meat delicatessen meat of wild animals. These meat products have a unique taste properties, as well as a large number of nutrients, and producing such products is very promising. With small fat venison meat has reduced energy performance, so it is recommended for expanding menu, and for cooking daily meals.
Keywords: energy value; game meat; енергетична цінність; amino acids; амінокислоти; кафедра технології м’яса і м’ясних продуктів